Peningkatan Pengetahuan Kebencanaan Siswa Sekolah Dasar Bekerjasama dengan Badan Penanggulangan Bencana Daerah Jawa Timur - Abdul Qodir; Ahmad Guntur Alfianto; Angernani Trias Wulandari; Dini Prastyo (I-Com: Indonesian Community Journal, 2023)
Indonesia, situated in a region with four tectonic plates, is highly susceptible to natural disasters. The government has enacted multiple policies and laws to assist in disaster management and to decrease the overall level of risk. A recent situational analysis of SDN Srigonco, located in Bantur sub-district, revealed that damage from a tornado had occurred in early 2023, and that there had not been any disaster training provided since 2018. Due to its location on the South Coast of Malang Regency, Srigonco Village faces an elevated risk of natural disasters, including earthquakes and tsunamis. Specifically, children are identified as one of the most vulnerable groups during disasters due to their limited understanding of the associated risks and inability to adequately prepare. Early disaster awareness is critical in reducing the impact of these risks. The component of school preparedness currently falls short of expectations. The teaching of disaster response and its impact on children, who are a vulnerable group, through simulations, could be a possible strategy to reduce disaster risks. Consequently, the objective is to provide disaster preparedness instruction to students at SDN 01 and 02 Srigonco in Malang District, fostering understanding and reducing disaster risks.